Essential algorithms a practical approach to computer algorithms - Stephens, Rod 1961- (Wiley, 2013)
A friendly and accessible introduction to the most useful algorithms Computer algorithms are the basic recipes for programming. Professional programmers need to know how to use algorithms to solve difficult programming problems. Written in simple, intuitive English, this book describes how and when to use the most practical classic algorithms, and even how to create new algorithms to meet future needs. The book also includes a collection of questions that can help readers prepare for a programming job interview. Reveals methods for manipulating common data structures s.
Print version record
Keywords: Computer algorithms; Data structures (Computer science); Pseudocode (Computer program language); Algorithms; Algorithmes; Structures de données (Informatique); Pseudocode (Langage de programmation); algorithms; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference; Computers and IT; Llibres electrònics